Implementation of Zero Trust Security in MSME Enterprise Architecture: Challenges and Solutions - Rahman, Abdul; Indrajit, Eko; Unggul, Akhmad; Dazki, Erick (Politeknik Ganesha Medan, 2024)
This research examines the implementation of Zero Trust Security in Enterprise Architecture in Micro, Small, and Medium Enterprises to improve cybersecurity. The background of this research focuses on the increasing cyber threats faced by MSMEs and their limitations in adopting advanced security systems. The purpose of this study is to evaluate the effectiveness of Zero Trust Security in protecting MSME data and information systems from internal and external threats, as well as identifying challenges and solutions in its implementation. The research method used is a case study on several MSMEs with a qualitative and quantitative approach involving in-depth interviews, surveys, and secondary data analysis. The results showed that the implementation of ZTS significantly improved information system security in MSMEs, with a 45% reduction in security incidents after ZTS adoption. In addition, ZTS was also shown to increase cybersecurity awareness among MSME employees. The main challenges identified include the need for adequate training, changes in organizational culture, and budget limitations. To overcome these challenges, this study recommends the adoption of continuous training strategies, increased cybersecurity awareness, and the utilization of affordable yet effective security solutions. The conclusion of this study confirms that Zero Trust Security is an effective and efficient approach to improving the cybersecurity of MSMEs. However, further research is recommended to explore the application of Zero Trust Security in various other industry contexts and to develop more affordable solutions for MSMEs with limited resources.